Organochlorine pesticide level in patients with chronic kidney disease of unknown etiology and its association with renal function - Rishila Ghosh; Manushi Siddarth; Neeru Singh; Vipin Tyagi; Pawan Kumar Kare; Basu Dev Banerjee; Om Prakash Kalra; Ashok Kumar Tripathi (Komiyama Printing Co. Ltd, 2017)
Abstract Background Involvement of agrochemicals have been suggested in the development of chronic kidney disease of unknown etiology (CKDu). The association between CKDu and blood level of organochlorine pesticides (OCPs) in CKDu patients has been examined in the present study. Methods All the recruited study subjects (n = 300) were divided in three groups, namely, healthy control (n = 100), patients with chronic kidney disease of unknown etiology (n = 100), and patients with chronic kidney disease of known etiology (CKDk) (n = 100). Blood OCP levels of all three study groups were analyzed by gas chromatography. Results Increased level of OCPs, namely α-HCH, aldrin, and β-endosulfan, were observed in CKDu patients as compared to healthy control and CKD patients of known etiology. The levels of these pesticides significantly correlated negatively with the estimated glomerular filtration rate (eGFR) and positively with urinary albumin of CKD patients. Logistic regression analysis revealed association of γ-HCH, p, p'-DDE, and β-endosulfan with CKDu on adjustment of age, sex, BMI, and total lipid content. Conclusions Increased blood level of certain organochlorine pesticides is associated with the development of chronic kidney disease of unknown etiology.